New species and records of Oxyethira Eaton (Trichoptera: Hydroptilidae) from Amazonas State, Brazil - Santos, Allan Paulo Moreira; Henriques-Oliveira, Ana Lucia; Nessimian, Jorge Luiz (Zootaxa, 2009)
Three new species of Oxyethira Eaton, 1873—O. luanae sp. nov., O. sinistra sp. nov., and O. longipenis sp. nov.—are described and illustrated from male specimens collected in Amazonas State, Brazil. Six described species are recorded for the first time from Brazil: O. circaverna Kelley, 1983, O. longissima Flint, 1974, O. macrosterna Flint, 1974, O. peruviana Harris & Davenport, 1999, O. picita Harris & Davenport, 1999, and O. presilla Harris & Davenport, 1999. Oxyethira tica Holzenthal & Harris, 1992, reported from Minas Gerais, Brazil, is now also recorded from Amazonas.